Improving Intercity Passenger Rail Planning using Evidence from Passenger Survey Data. Issue 10 (December 2018) - Sperry, Benjamin R.; Collins, Tyler
Federal mandates require that states develop comprehensive state rail plans that clarify a vision for the role of intercity passenger rail services in the state's transportation system and a program of projects necessary to achieve that vision. In that context, this paper presents an analysis of more than 10, 000 surveys obtained during the past 10 years from passengers of five U.S. state-supported intercity passenger rail routes. The purpose of the analysis is to support the development of state rail plans by gaining valuable insight into passenger behavior, the market area for passenger rail services, and the broader mobility impacts of passenger rail services. The market area analysis found that approximately three-quarters of rail passengers live within 30 mi of a rail station, affirming the use of this distance as a radius for planning purposes. The mobility analysis indicated that automobile is the primary alternative to passenger rail services among passengers of the five routes; statistical models of alternative mode preference yielded significant insight into strategies that states can implement to increase the mode shift of automobile and airplane passengers to rail services. The findings and recommendations of this paper can be used by planners and policymakers to implement a practical yet data-driven approach to the development of passenger-related components of state rail plans, providing a clear linkage between investment strategies and statewide mobility goals.